Succession of transiently active tumor‐initiating cell clones in human pancreatic cancer xenografts. Issue 7 (19th May 2017) - Ball, Claudia R; Oppel, Felix; Ehrenberg, Karl Roland; Dubash, Taronish D; Dieter, Sebastian M; Hoffmann, Christopher M; Abel, Ulrich; Herbst, Friederike; Koch, Moritz; Werner, Jens; Bergmann, Frank; Ishaque, Naveed; et al.
Abstract: Although tumor‐initiating cell (TIC) self‐renewal has been postulated to be essential in progression and metastasis formation of human pancreatic adenocarcinoma (PDAC), clonal dynamics of TICs within PDAC tumors are yet unknown. Here, we show that long‐term progression of PDAC in serial xenotransplantation is driven by a succession of transiently active TICs producing tumor cells in temporally restricted bursts. Clonal tracking of individual, genetically marked TICs revealed that individual tumors are generated by distinct sets of TICs with very little overlap between subsequent xenograft generations. An unexpected functional and phenotypic plasticity of pancreatic TICs in vivo underlies the recruitment of inactive TIC clones in serial xenografts. The observed clonal succession of TIC activity in serial xenotransplantation is in stark contrast to the continuous activity of limited numbers of self‐renewing TICs within a fixed cellular hierarchy observed in other epithelial cancers and emphasizes the need to target TIC activation, rather than a fixed TIC population, in PDAC. Synopsis: Molecular tracking of single tumor initiating cells (TIC) of pancreatic ductal adenocarcinoma (PDAC) xenografts in vivo reveals the functional and phenotypic plasticity of transiently active TIC producing temporally restricted tumor cell bursts. PDAC TIC are functionally and phenotypically plastic. Transiently active PDAC TIC produce tumor cells in a succession of temporally restricted bursts. Long‐term progression of pancreatic cancer is driven by functional plasticity. Abstract : Molecular tracking of single tumor initiating cells (TIC) of pancreatic ductal adenocarcinoma (PDAC) xenografts in vivo reveals the functional and phenotypic plasticity of transiently active TIC producing temporally restricted tumor cell bursts.